Pengembangan Media Pembelajaran Fisika Menggunakan Corel Video Studio Pro X 7 Pada Materi Teori Kinetik Gas - hade, liib; aswirna, prima (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The background of this research is that the media often used by educators is only visual, so abstract material cannot be concretized. Educators explain the material only with media in the form of whiteboards, markers, props and occasionally use power points. The learning process like this causes students to feel bored to take part in learning. The purpose of this study is to produce physics learning media using Corel Video Studio X 7 on the valid, practical and effective kinetic theory of gas material. This research is research and development (R & D). The design of the development of physics learning media using Corel Video Studio Pro X 7 on the material of Gas Kinetic Theory is using the 4D development model including: 1) define phase; 2) planning phase; and 3) develop and last stage disseminate. The instruments used in this study were validity questionnaire, practical questionnaire, and effectiveness questionnaire. The media validity test is given to 5 expert validators assessed from the material / content, media / construction, and language aspects. Practicality tests are given to educators and students, while the effectiveness test is given to students. The result of the research is that physics learning media has been produced using the valid, practical and effective Corel Video Studio Pro X 7 application.